Pragmatism and idealism - Caldwell, William, 1863-1942 (Salt Lake City, UT : Project Gutenberg, 2023)
"Pragmatism and Idealism" by William Caldwell is a philosophical examination written in the early 20th century. The work explores the intricacies of Pragmatism, its connections to Idealism, and the broader philosophical discourse of the time. Caldwell delves into the development of Pragmatism, discussing its implications for human thought and society, and critiques the limitations of Rationalism. The opening portion of the book introduces Pragmatism, outlining its historical backdrop and how it has gained prominence in philosophical circles. Caldwell discusses the foundational ideas that Pragmatism hinges on, such as the view that truth is subjective and shaped by human experience and practicality, contrasting it with Rationalism. He highlights key figures in the Pragmatist movement, including William James and John Dewey, and asserts that while Pragmatism emphasizes human action and utility, it also grapples with criticisms and challenges it faces in establishing a coherent philosophical account. The author sets the stage for a deeper analysis of Pragmatism's interplay with other philosophical doctrines, particularly within the context of modern societal issues. (This is an automatically generated summary.)
Release date is 2023-11-08
Chris Curnow and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Idealism; Pragmatism